Magnetic Domain Walls Moving in Curved Permalloy Nanowires under Continuous and Pulsed Fields - Hoang, Duc-Quang; Cao, Xuan-Huu; Nguyen, Hoai-Thuong; Dao, Vinh-Ai (Communications in Physics, 2021)
Magnetic domain walls created and propagated in curved permally nanowires under continuous and pulsed fields in a Lorentz microscope. Using such nanowires aims to create a single or multiple magnetic domain walls in typical areas of those structures, an external magnetic field then applies along the long axis of these nanowires. Following that the created domain walls are propagated from one end to the other end of each wire by increasing the continuous/pulsed field strength. At each increased field value, a Fresnel image is recorded. The obtained results show that the characteristics of those created and propagated domain walls are dependent on various parameters, i.e. connecting structures, wall types and chiralities. Corners between the straight and linking sections of those curved nanowires also play a crucial role along witth the local defects created in these wire-edges and surfaces where a point-defect is considered as a potential well that could pin/distort those created/propagated domain walls. By the aid of this observations, the dynamic properties of domain walls with the creating and propagating processes in those curved nanowires are exposed. These outcomes are vital to design novel domain wall trap structures supporting reproducible domain wall motions. That are of interest in providing a better understanding of multiple bits moving in the furure 3D racetrack memory, logic gates, shift register and other spintronic/computing devices.